IMPLEMENTASI KONVENSI MINAMATA DALAM PRAKTIK PENAMBANGAN EMAS DI KABUPATEN KUANTAN SINGINGI - Sapry, Hanna Zikria; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research analyses how the implementation of an international environmental regime, namely the minamata convention in mining practises in Kuantan Singingi Regency through policies implemented by the government. Gold mining practises in the quantity often involve the use of mercury in the gold extraction process, and can potentially damage the environment and health for humans. The Minamata Convention, which aims to reduce the use and impact of mercury around the world, has a significant impact here. This research examines the implementation of the Minamata Convention in gold mining practises in Kuantan Regency by considering difficulties, successes, and policies to increase compliance and its positive impact on the local community and the environment. This research uses a qualitative method, by using data collection techniques through literature studies sourced from several books, journals, articles, websites as well as sampling directly to the field. This research uses the perspective of constructivism, the level of analysis: the nation state and the theory of government piracy. The results of this study show that the collaboration between local governments and international regimes goes well through various programs. However, the big problem still exists. This includes the interests of local communities that rely on traditional mining, uncertainty about technological and scientific alternatives, and a lack of consistent law enforcement. The results of laboratory analysis showed that the mercury content in the water sample was below the detection limit, while the soil sample was 0.0761 mg/kg, this showed that there was residual mercury in the soil even though it was below the threshold set by the government. this shows that there is residual mercury in the soil even though it is below the threshold that has been set by the government as a sign of successful reduction in the use of mercury Keywords: Minamata Convention, Policy, Gold Mining, Mercury